Reactive versus Latching Phase Control of a Two-body Heaving Wave Energy Converter - Falcão, António F. de O. (2010)
The paper deals with the modelling, optimization and control of the IPS buoy wave energy converter, a two-body point-absorber oscillating in heave, consisting of a floater rigidly connected to a long submerged vertical acceleration tube open at both ends within which a piston can slide, forcing the motion of the inside water below and above it. Energy is converted from the relative motion between the piston and the buoy-tube pair. The modelling is performed in the frequency domain (including reactive phase control), in order to provide some kind of geometry optimization, and also in the timedomain to allow the simulation of a more realistic highpressure- oil power take-off system.